2020
DOI: 10.3390/brainsci10040196
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality of Brain Infarction Patients and Red Blood Cell Distribution Width

Abstract: Background: Meta-analysis has found that high baseline red blood cell distribution width (RDW) is associated with increased long-term mortality (mortality at one year or more) in ischemic stroke. The objectives of this study were to determine whether there is an association between RDW and 30-day mortality, and to explore whether RDW during the first week of ischemic stroke could be a 30-day mortality biomarker. Methods: We included patients with malignant middle cerebral artery infarction (MMCAI). RDW at days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…One of the strengths of the study is that the association between RDW at ICU admission and mortality was found in all regression models, and that this association is in line with the results we found in previous studies in septic or cerebral ischemic patients [22] , [23] , as well as the results found by other researchers in patients with coronary heart disease [18] , liver disease [19] or pancreatitis [20] .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One of the strengths of the study is that the association between RDW at ICU admission and mortality was found in all regression models, and that this association is in line with the results we found in previous studies in septic or cerebral ischemic patients [22] , [23] , as well as the results found by other researchers in patients with coronary heart disease [18] , liver disease [19] or pancreatitis [20] .…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have showed an association between RDW and inflammatory cytokines as tumour necrosis factor (TNF)-alpha, interleukin (IL)-1 and IL-6 [31] , [32] , and between RDW and oxidative stress [32] , [33] . Previously, we have reported in patients with sepsis [23] or brain infarction [22] an association between RDW and blood levels of TNF-alpha and malondialdehyde (which appears by lipid peroxidation of cellular membrane phospholipids). We speculated that the association between RDW and mortality of COVID-19 patients found in our study could be due to a higher degree of inflammation and oxidation in those patients who end up dying.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is commonly used to identify different types of anemia and reactive bone marrow states and it is also a simple, widely used, and inexpensive parameter. In recent years, some clinical studies have shown that there is a correlation between RDW and some acute diseases, such as brain infarction, sepsis, infective endocarditis and diabetic ketoacidosis 7 11 . In addition, several studies have reported the predictive effect of RDW on lung disease 12 16 , while the predictive effect of RDW on acute respiratory failure has not been reported.…”
Section: Introductionmentioning
confidence: 99%